CHARACTERISTICS OF THE IMMUNE STATUS OF CHILDREN WITH DIAGNOSED ALLERGIC DISEASES - Solibaeva N. O.; Yuldashov I. R. (The Conference Hub, 2025)
Despite the extensive study of the impact of exogenous factors on the development of allergic diseases in children depending on climatic and geographical conditions, the mechanism underlying immune dysfunction in children in the Namangan region of the Republic of Uzbekistan remains unclear. Information on the development of immunological diseases in children under the influence of living and climatic conditions on the immune system has not been studied. Furthermore, there is insufficient data on the relationship between immune dysfunction itself and chronic diseases in the population of this region.